PEDAGOGICAL FEATURES OF THE PREVENTION OF YOUTH OFFENSES - Ostonov Jasur Shopirjonovich; Bafoyev Shahzod Najmiddin o‘g‘li (Web of Journals Publishing, 2024)
This article provides information on the pedagogical and psychological laws of legal and educational work, as well as the psychological analysis of offenses committed by young people, the stages of its formation, and the general analysis of existing psychological approaches to these cases.
Keywords: Deviance, legal-educational work, legal culture, communicative-valuable, reflexive-corrective, science, education.